2013
DOI: 10.1002/jgra.50340
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric tidal effects on the ionospheric midlatitude summer nighttime anomaly using SAMI3 and TIEGCM

Abstract: [1] This paper is the first study to employ a three-dimensional physics-based ionosphere model, SAMI3, coupled with the National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) and Global Scale Wave Model to simulate the mesospheric and lower thermospheric tidal effects on the development of midlatitude summer nighttime anomaly (MSNA). Using this coupled model, the diurnal variation of MSNA electron densities at 300 km altitude is simulated on both Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 55 publications
7
47
0
Order By: Relevance
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionsupporting
confidence: 74%
“…At ionosphere mid-latitudes, the nighttime electron density enhancement has been observed and reported by previous studies (e.g., Bailey et al 1991;Farelo et al 2002;Dabas and Kersley 2003;Luan et al 2008;Park et al 2008;Chen et al 2011Chen et al , 2012Chen et al , 2013Lin et al 2011;Rajesh et al 2016). This density-enhanced ionospheric feature appeared more frequently during solar minimum conditions (Bailey et al 1991), and it is suggested to be caused by larger downward plasma flux from the plasmasphere during the nighttime (Mikhailov et al 2000;Farelo et al 2002;Dabas and Kersley 2003).…”
Section: Introductionsupporting
confidence: 74%
“…As the E × B drift mainly affects the F region at equatorial latitudes, it will not be important for the longitudinal wave patterns of the plasma at midlatitudes. However, the wave patterns of the MSNA as reported by Chen et al (2013) and Xiong and Lühr (2014) imply that there should be some other coupling mechanism at midlatitudes. By model simulations, Jones Jr. et al (2013) revealed that at low and middle latitudes the nonmigrating tides of the zonal wind could be generated in situ through ion-neutral interactions due to the longitudinal ionospheric density variations imposed by the actual geomagnetic field configuration.…”
Section: Zonal Wind Observations and Model Predictionsmentioning
confidence: 89%
“…Other mechanisms such as the transportation of plasma from the dayside ionosphere and the downward flux from the plasmasphere have also been proposed (Burns et al, 2008). By employing a three-dimensional physics-based ionosphere model, SAMI3 (Sami3 is Also a Model of the Ionosphere), coupled with the Thermosphere-Ionosphere Electrodynamics General Circulation Model (TIE-GCM) and the Global Scale Wave Model, Chen et al (2013) reported a clear eastward movement of the southern MSNA (see their Fig. 2b).…”
Section: Introductionmentioning
confidence: 97%
“…Wu et al, 2012). At middle latitude Chen et al (2013) reported an eastward propagating wave 1 pattern of the Weddell Sea Anomaly (WSA) by using the SAMI3 (Sami3 is Also a Model of the Ionosphere) model combined with the Thermosphere-Ionosphere Electrodynamics General Circulation Model (TIEGCM) and the Global-Scale Wave model simulations. Based on the in situ electron density measurements from CHAMP and GRACE satellites, found a prominent longitudinal WN2 pattern in the northern middle latitudes during local summer.…”
Section: Y-l Zhou Et Al: Solar Activity Dependence Of Nonmigratingmentioning
confidence: 99%